(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the hemodynamic status of fasting emergency service professionals by measuring the inferior vena cava collapsibility index (IVCCI) using bedside ultrasonography and the perfusion index (PI) using a noninvasive method and examining the relationship between these two parameters.Materials and Methods: This was a prospective cross-sectional study. The IVCCI and PI were measured in emergency service professionals at 11:00 am, 07:00 pm, and 10:00 pm between May 16 and June 4, 2018, corresponding to the 11th and 20th days of Ramadan. IVCCI and PI levels at different times of fasting and after feeding were compared.Results: The IVCCI-2 value of the volunteers at the 16th hour of fasting was significantly higher than the IVCCI-1 value at the 8th hour of fasting (p 0.001). The IVCCI-3 value at the postprandial 2nd hour after eating was significantly lower than both the average IVCCI-1 at the 8th hour of fasting (p 0.001) and average IVCCI-2 at the 16th hour of fasting (p 0.001). The PI-2 value at the 16th hour of fasting was significantly lower than the PI-1 value at the 8th hour of fasting. The PI-3 value at the postprandial 2nd hour after eating was significantly higher than both the average PI-1 at the 8th hour of fasting (p = 0.001) and the average PI-2 at the 16th hour of fasting (p 0.001).Conclusion: The collapsibility increased at the longest time of fasting, and the collapsibility ratio decreased after eating. Similarly, PI was the lowest at the longest time of fasting, whereas PI increased after eating.